The relationship between chromosome structure and function at a human telomeric region. - Flint, J; Thomas, K; Micklem, G; Raynham, H; Clark, K; Doggett, N; King, A; Higgs, D (1997)
We have sequenced a contiguous 284,495-bp segment of DNA extending from the terminal (TTAGGG)n repeats of the short arm of chromosome 16, providing a full description of the transition from telomeric through subtelomeric DNA to sequences that are unique to the chromosome. To complement and extend analysis of the primary sequence, we have characterized mRNA transcripts, patterns of DNA methylation and DNase I sensitivity. Together with previous data these studies describe in detail the structural and functional organization of a human telomeric region.